Occupational class and risk of hepatitis B and C viral infections: A case-control study-based data from a nationwide hospital group in Japan. Issue 12 (December 2022) - Nakazawa, Shoko; Fukai, Kota; Furuya, Yuko; Hoshi, Keika; Kojimahara, Noriko; Toyota, Akihiro; Korenaga, Masaaki; Tatemichi, Masayuki
Abstract: Background: Occupational class, a proxy for socio-economic status, is a known factor for health disparities. However, no study has reported the association between occupational class and the risk of viral hepatitis B and C (HBV/HCV) infections. We investigated the effects of occupational class on the prevalence of HBV/HCV infections. Methods: This is an unmatched hospital-based case-control study that included 12, 101 patients who were diagnosed with HBV infection (ICD–10, B16.0, B16.1, B16.2, B16.9, B17.0, B18.0, B18.1) or HCV infection (ICD–10, B17.1, B18.2) and 698, 168 controls (those with non-HBV/HCV-related diseases) aged ≥ 20 years who were initially hospitalized between 2005 and 2019. Patients were categorized according to occupational class (blue-collar, service, professional, and manager) and industrial sector (blue-collar, service, and white-collar). Managers in the blue-collar industry were set as the reference group, and the odds ratios (ORs) for the risk of HBV and HCV infections were calculated. Results: Occupational class was significantly associated with only HCV infection risk. Professionals in all industrial sectors showed the lowest risk for HCV (OR (95% confidence intervals [CIs]) = 0.69 [0.58–0.82] in the blue-collar industry, 0.52 [0.38–0.73] in the service industry, and 0.60 [0.52–0.70] in the white-collar industry). Further, after adjusting for sex, age, and region of admitting hospital, all occupational classes in the white-collar industry showed lower risks of HCV than those in the other industries (ORs= 0.58 [0.47–0.71] in blue-collar workers, 0.74 [0.64–0.84] in service workers, 0.60 [0.52–0.70] in professionals, and 0.81 [0.64–1.02] in managers in white-collar industry). Conclusions: Occupational class was closely associated with HCV infection risk only. Considering that blue-collar workers in the white-collar industry also showed a low risk, adequate measures should be taken against hepatitis, possibly because of the screening tests and cure implemented in that population.